Assessing Risk for Bycatch and Byproduct Species Using a Modified Sustainability Assessment for Fishing Effects (SAFE) Approach - Grant J. Johnson; Jonathan J. Smart; Vinay Udyawer; Rik C. Buckworth; Clive R. McMahon; Chalie Huveneers (Fish and Fisheries, 2026)
Central to ecosystem‐based fisheries management is ensuring the sustainability of bycatch and byproduct species. However, the sustainability of these species is difficult to assess as the lack of information limits the use of traditional stock assessment methods. We demonstrate, using a complex multi‐species fisheries exemplar, the efficient assessment of large numbers of diverse species, using a modified Sustainability Assessment for Fishing Effects (SAFE) approach. Applying this technique to 256 teleost and elasmobranch species caught in Australia's Northern Territory Demersal and Timor Reef Fisheries, we first applied an initial screening assessment to identify at‐risk species followed by a secondary SAFE assessment for a more detailed evaluation. To enhance the precision of the secondary assessment, we incorporated species distribution modelling and refined fishing footprint estimates through spatial analysis of trawl paths, from vessel monitoring system data. Additionally, we integrated Monte Carlo simulations into the SAFE process to quantify uncertainties in fishing footprint and capture efficiency parameters. The conservative criteria applied in the initial screening process assessed 208 species as low‐risk, with the remaining 48 species evaluated through our modified secondary SAFE approach. These 48 species were also subsequently classified as low‐risk. Our approach adds steps to the SAFE process but enables us to efficiently assess large numbers of diverse species and thereby allows resources to be allocated to those species most at‐risk. This adaptable approach is readily modifiable for application in other fisheries, including those with no or limited effort and catch data.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Elevated CO 2 interacts with nutrient inputs to restructure plant communities in phosphorus‐limited grasslands - Christopher R. Taylor; Luke C. England; J. Ben Keane; Jessica A. C. Davies; Jonathan R. Leake; Iain P. Hartley; Simon M. Smart; Victoria Janes‐Bassett; Gareth K. Phoenix (Global Change Biology, 2024)
Globally pervasive increases in atmospheric CO 2 and nitrogen (N) deposition could have substantial effects on plant communities, either directly or mediated by their interactions with soil nutrient limitation. While the direct consequences of N enrichment on plant communities are well documented, potential interactions with rising CO 2 and globally widespread phosphorus (P) limitation remain poorly understood. We investigated the consequences of simultaneous elevated CO 2 (eCO 2 ) and N and P additions on grassland biodiversity, community and functional composition in P‐limited grasslands. We exposed soil‐turf monoliths from limestone and acidic grasslands that have received >25 years of N additions (3.5 and 14 g m −2 year −1 ) and 11 (limestone) or 25 (acidic) years of P additions (3.5 g m −2 year −1 ) to eCO 2 (600 ppm) for 3 years. Across both grasslands, eCO 2 , N and P additions significantly changed community composition. Limestone communities were more responsive to eCO 2 and saw significant functional shifts resulting from eCO 2 –nutrient interactions. Here, legume cover tripled in response to combined eCO 2 and P additions, and combined eCO 2 and N treatments shifted functional dominance from grasses to sedges. We suggest that eCO 2 may disproportionately benefit P acquisition by sedges by subsidising the carbon cost of locally intense root exudation at the expense of co‐occurring grasses. In contrast, the functional composition of the acidic grassland was insensitive to eCO 2 and its interactions with nutrient additions. Greater diversity of P‐acquisition strategies in the limestone grassland, combined with a more functionally even and diverse community, may contribute to the stronger responses compared to the acidic grassland. Our work suggests we may see large changes in the composition and biodiversity of P‐limited grasslands in response to eCO 2 and its interactions with nutrient loading, particularly where these contain a high diversity of P‐acquisition strategies or developmentally young soils with sufficient bioavailable mineral P.

Constructed Wetlands Suitability for Sugarcane Profitability, Freshwater Biodiversity and Ecosystem Services - Adam D. Canning; James C. R. Smart; Joshua Dyke; Graeme Curwen; Syezlin Hasan; Nathan J. Waltham (Environmental Management, 2023)
Freshwater ecosystems, such as wetlands, are among the most impacted by agricultural expansion and intensification through extensive drainage and pollution. There is a pressing need to identify ways of managing agricultural landscapes to ensure food and water security without jeopardising biodiversity and other environmental benefits. Here we examine the potential fish biodiversity and landholder financial benefits arising from the integration of constructed lagoons to improve drainage, flow regulation and habitat connectivity within a sugarcane dominated catchment in north Queensland, Australia. A hybrid approach was used, combining the findings of both fish ecological surveys and a financial cost-benefit analysis. We found that the constructed lagoons supported at least 36 native freshwater fishes (over half of all native freshwater fishes in the region), owing to their depth, vegetated margins, moderate water quality and high connectivity to the Tully River. In addition to biodiversity benefits, we estimated that surrounding sugarcane farms would have financially benefited from reduced flooding of cropland and the elevation of low-lying cropland with deposited spoil excavated from lagoon construction. Improved drainage and flow regulation allowed for improvement in sugarcane yield and elevated land increased gross margins from extending the length of the cane production cycle or enabling a switch from cattle grazing to cane production. Restoring or creating wetlands to reduce flooding in flood-prone catchments is a globally applicable model that could improve both agricultural productivity and aquatic biodiversity, while potentially increasing farm income by attracting payments for provision of ecosystem services.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Identifying and mitigating risks to completion of small grant climate change adaptation projects: evidence from the Pacific - Syezlin Hasan; Christopher M. Fleming; James C. R. Smart; Andrew J. Buckwell; Maja Vinde Folkersen; Brendan Mackey (Regional Environmental Change, 2021)

Identifying and prioritising adaptation options for a coastal freshwater supply and demand system under climatic and non-climatic changes - Thuc D. Phan; James C. R. Smart; Oz Sahin; Ben Stewart-Koster; Wade L. Hadwen; Samantha J. Capon (Regional Environmental Change, 2020)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Using a choice experiment and birder preferences to guide bird‐conservation funding - Rochelle Steven; James C. R. Smart; Clare Morrison; J. Guy Castley (Conservation Biology, 2017)
Conservation of biodiversity, including birds, continues to challenge natural‐area managers. Stated‐preference methods (e.g., choice experiment [CE]) are increasingly used to provide data for valuation of natural ecosystems. We used a CE to calculate birders’ willingness to pay for different levels of bioecological attributes (threatened species, endemic species, and diversity) of birding sites with hypothetical entry fees. The CE was delivered at popular birding and avitourism sites in Australia and the United Kingdom. Latent‐class modeling results revealed heterogeneous preferences among birders and correspondingly variable willingness to pay. Four clear groups were apparent: quantity‐driven birders, special‐birds seekers, confused respondents, and price‐is‐no‐object birders. Quantity‐driven birders were attracted to sites that deliver high levels of diversity and endemic species for which they were willing to pay $135 and $66 to visit, respectively, above what they were willing to pay to visit a site with low levels of diversity and few endemic and threatened species . Special‐bird seekers valued threatened species and high levels of endemic species most (willingness to pay $45 and $46, respectively). Confused respondents’ preferences were difficult to determine, but they were the most sensitive to the hypothetical entry fees, unlike the price‐is‐no‐object birders, who were not at all sensitive to cost. Our findings demonstrate that birders are amenable to paying for their preferred birding experience. These payments could provide an alternative source of funding in some avitourism sites on both public and private land. Such alternative revenue streams should be explored and given full consideration in increasingly competitive conservation‐financing environments.

DIMBOA levels in hexaploid Brazilian wheat are not associated with antibiosis against the cereal aphids Rhopalosiphum padi and Sitobion avenae - Jorge F. Pereira; André L. F. Sarria; Stephen J. Powers; Gudbjorg I. Aradottir; John C. Caulfield; Janet Martin; Lesley E. Smart; John A. Pickett; Michael A. Birkett; Paulo R. V. S. Pereira (Theoretical and Experimental Plant Physiology, 2017)